Offshore Wind Farm Impact Assessment on Radio Systems Operating in the MF Band - Krzysztof Bronk; Patryk Koncicki; Adam Lipka; Rafał Niski; Błażej Wereszko (Energies)
This paper discusses the impact of wind farms on systems operating in the MF band. The presented material has been gathered by the authors during several measurement campaigns they conducted in recent years on the premises of various land wind farms in northern Poland. The results of this research, however, are particularly important and relevant in the context of offshore wind farms, since several radio systems crucial for safety of navigation and life at sea operate in the MF band, most notably components of the GMDSS. At the time of writing, however, no OWFs existed yet at the Baltic Sea in the Polish Exclusive Economic Zone; therefore, it was not possible to conduct such measurements in the target area under maritime conditions. This article presents the theoretical backgrounds of the topic, and then introduces the results obtained for the lower part of the MF band (DGPS) and the upper part of this band. The results obtained in the latter case can be directly applied to the higher frequencies of the LF band and the lower frequencies of the HF band as well. The results show that the impact of wind farms (in the context of EMF, radio shadowing, and interference) on those bands is minimal or even negligible, which is an important and positive conclusion in the context of extensive development of OWFs in Polish waters scheduled for the next few years.